"I just feel comfortable out here, there's something about the place": staff and client perceptions of a remote Australian Aboriginal drug and alcohol rehabilitation service - Alice Munro; Julaine Allan; Anthony Shakeshaft; Courtney Breen (BMC, 2017)
Abstract Background The need for effective, culturally safe residential rehabilitation services for Aboriginal people is widely acknowledged, however the combination of treatment components that is optimally effective, is not well defined. Most existing Aboriginal residential rehabilitation research has focused on describing client characteristics, and largely ignored the impact of treatment and service factors, such as the nature and quality of therapeutic components and relationships with staff. Methods This qualitative study was undertaken as part of a three-year mixed methods community-based participatory research (CBPR) project that aimed to empirically describe a remote Aboriginal drug and alcohol rehabilitation service. Researchers utilised purposive sampling to conduct 21 in-depth, semi-structured interviews. The interviews used a 'research yarning' approach, a form of culturally appropriate conversation that is relaxed and narrative-based. The interview transcripts were thematically coded using iterative categorization. The emerging themes were then analysed from an Interpretative Phenomenological Analysis, focusing on how participants' lived experiences before and during their admission to the service shaped their perceptions of the program. Results A total of 12 clients (mean age 35 years, SD 9.07, 91% Aboriginal) and 9 staff (2 female, 7 male, mean age 48 years, SD 8.54, 67% Aboriginal) were interviewed. Five themes about specific program components were identified in the interview data: healing through culture and country; emotional safety and relationships; strengthening life skills; improved wellbeing; and perceived areas for improvement. This research found that Aboriginal drug and alcohol residential rehabilitation is not just about length of time in treatment, but also about the culture, activities and relationships that are part of the treatment process. Conclusion This study highlights that cultural elements were highly valued by both clients and staff of a remote Aboriginal residential rehabilitation service, with the country or location being fundamental to the daily practice of, and access to, culture. Developing reliable and valid assessments of the program components of culture and treatment alliance would be valuable, given this study has reinforced their perceived importance in achieving positive treatment outcomes. Further, strengthening the aftercare program, as part of an integrated model of care, would likely provide greater support to clients after discharge.